Do people in income poverty use their income efficiently? A subjective well-being approach - Mariano Rojas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
A subjective well-being approach is followed to assess the magnitude of inefficiency in the use of income. The information comes from a Mexican survey and an X-inefficiency technique is used. The paper shows that there exists substantial inefficiency in the use of income at all income levels, even for those in income poverty. It is shown that inefficiency is significantly related to practices, attitudes, and motivations for consuming. Economic theory has focused on rising people's income to increase their economic well-being; this paper shows that reducing inefficiency in the use of income is an alternative instrument which deserves further consideration.
Keywords: D1; D11; D12; D13; D61; I31; 330; subjective well-being; economic satisfaction; X-inefficiency; income poverty; Mexico; Armut; Zufriedenheit; X-Effizienz; Mexiko